2011
DOI: 10.1002/anie.201102030
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Functionalization of Silica‐Encapsulated Yeast Cells

Abstract: Tough shell: Living yeast cells can be simultaneously silica‐encapsulated and thiol‐functionalized by polycondensation of silicic acid and (3‐mercaptopropyl)trimethoxysilane under mild conditions. Various functions such as fluorescent dyes (see picture; green: fluorescein, red: rhodamine), chemical moieties, or proteins, can be introduced to the artificial shell by using maleimide‐based coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 55 publications
0
67
0
Order By: Relevance
“…The multilayer deposition was initiated with positively charged GO-NH þ 3 nanosheet to enhance the electrostatic interaction because the native yeast cells were known to present highly negative charge. [15][16][17] It is obvious that deposition of oppositely charged GO nanosheet would change the surface charge of the yeast cells. The surface charge, therefore, was individually measured with the progress of the deposition of GO-NH þ 3 and GO-COOnanosheets on the yeast cells from the first layer to the fifth layer ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The multilayer deposition was initiated with positively charged GO-NH þ 3 nanosheet to enhance the electrostatic interaction because the native yeast cells were known to present highly negative charge. [15][16][17] It is obvious that deposition of oppositely charged GO nanosheet would change the surface charge of the yeast cells. The surface charge, therefore, was individually measured with the progress of the deposition of GO-NH þ 3 and GO-COOnanosheets on the yeast cells from the first layer to the fifth layer ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…We, therefore, investigated the viability of yeast@GO by using FDA, which examined the activity of intracellular esterases and emitted green fluorescence by reactive oxygen species; yeast cells in green were considered alive, and the others were considered dead. [16,18,19] Viability test indicated that the GO nanosheet encapsulation was compatible with living yeast cells as shown in Figure 2. Moreover, the permeability to FDA implied that GO multilayer shell would be permeable to small molecules such as water or nutrients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our synthetic approach could be applied to the interdisciplinary fields, specifically related to living cells, such as nanobiotechnology, biomedical applications, and cell-based nano/micro devices, because these applications require the cytocompatible process to integrate low cytotoxic materials with cell surfaces. [19][20][21][22] In addition, the silicification carried Notes out in the synergistic fashion could be another tool for investigating silicification mechanisms in nature.…”
mentioning
confidence: 99%